Selected water parameters from a buffer sone in the NW Panay Conservation Area. - Magdaug, Robert L. (2002.)
Water samples were taken from seven sampling sites in Barangay Cubay, Libertad, Antique and analyzed for selected physico-chemical parameters. Recommended limits set by the EEC, WHO, and the Canadian Water Quality Guidelines were followed., Dissolved oxygen is from 4.03 to 7.76 mg/l. Phosphate-P concentrations range from 0.029 to 0.215 mg/l. Nitrate-N is from 2.34 to 2.75 mg/l. The pH of the samples range from 6.97 to 8.30. The total alkalinity, equal to the MO alkalinity, is from 56.7 to 82.0 mg/L as CaCO3. The total acidity, equal to its phenolphthalein acidity, is from 2.8 to 7.8 mg/L as CaCO3. The hardness ranges from 54.6 to 130.9 mg/L as CaCO3. The evaporation residue was from 200.0 to 258.7 mg/L. Filterable substances were negligible. Ash content of the water samples range 96.7 to 168.7 mg/L. Chloride is from 5.19 to 8.15 mg/L. Total salt content range from 678.9 to 748.5 mg/L as Na. Sodium was found at 5 mg/L in all the water samples. The soluble sodium percent (SSP) value is from 0.668 to 0.737. Qualitative analysis of cations detected the presence of iron, calcium and magnesium. Total iron ranged from 0.100 to 0.156 mg/L. Statistical analysis shows that the water in all the sampling sites were all significantly different. The results show that the water from Barangay Cubay is within the recommend limits. The water is not objectionable for domestic and agricultural applications.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Buffer Zone -- New Washington Conservation Area